(3JjSjQ GdGSJYOGO dQJHI GdGLJgGOs - (3YHO Gddg Hf YHO GdQMef Hf YHO Gddg Hf eMeO GdbQTj GdgGeTj, HgGA GdOjf GHf Ybjd,J (B769 (3g` s
(3ChdgG (B:s
(3GdcdGe Ydi MLQ GdGSJfMGA s
(3BNQgG (B:s
(3GdcdGe Ydi eSM GdQGS s
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B96 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B70s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B342 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B297 s
Keywords: (3Gdabg GdTGaYjs